Impact of Shadow Economy on Tax Revenue in Sub-Saharan Africa - Idris, Adamu Adamu; Yusuf, Ismaila; Ekundayo, Olusegun Oyindamola; Abdulateef, Yunusa (FUDMA Journal of Accounting and Finance Research [FUJAFR], 2024)
This study tends to focus on how shadow economy and trade openness influence tax revenue in the Sub-Saharan Africa (SSA). The study used four SSA countries to test this relationship from 1991 to 2017. The study employs pool OLS with robust standard error to address the potential threat of heteroscedasticity. The result from this estimation indicate that shadow economy diminished the amount of tax revenue generated by these countries. Thus, the study recommends that appropriate measures should be put in place to curtail the size of the shadow economy because of its detrimental effects on tax revenue.
Keywords: Shadow Economy; Trade Openness; Tax Revenue